From subsistence to market-oriented farming: The role of groundwater irrigation in smallholder agriculture in eastern India - Pallavi Rajkhowa (Food Security, 2024)
Abstract Empowering smallholder farmers in low and middle-income countries (LMICs) and improving their livelihood is a critical goal for poverty reduction. To achieve this, agricultural commercialization can play an important role. However, a prerequisite to achieving agricultural commercialization is access and control of stable irrigation. This study revisits empirically the relationship between groundwater irrigation and crop commercialization. It also analyses the underlying mechanisms of how groundwater affects crop commercialization through on-farm production diversity. Studying the effects of groundwater irrigation on crop commercialization is essential for comprehending the trade-off between agricultural benefits and the environmental costs of groundwater irrigation. Geospatial and remote sensing information, combined with primary household data from small-scale farmers in eastern India, are employed in conjunction with an instrumental variable technique and a 3SLS simultaneous equation model for the analysis. The results suggest that small-scale farmers in eastern India experience enhanced crop commercialization when they have access to groundwater irrigation. Furthermore, the study suggests that the utilization of groundwater irrigation indirectly promotes crop commercialization by incentivizing farmers to diversify their production system.
Additional information: Q11;Q13
Keywords: 330; Irrigation; Market-oriented farming; Production diversity; India